Padrão da distribuição espacial e a estrutura de rede social dos casos de hanseníase em menores de 15 anos em Sobral, Ceará - Linhares, Maria Socorro Carneiro (2021)
eprosy, a disease caused by the bacillus Mycobacterium leprae, is still resistant to strategies for its elimination as a public health problem in the world. Studies with spatial analysis techniques and social networks have been used to increase knowledge and understanding of the dynamics of disease transmission in hyperendemic areas. The general objective of this study was to analyze the pattern of spatial distribution and the social network structure of leprosy cases in children under 15 years old in Sobral - Ceará, from 2014 to 2015. This is a descriptive and cross-sectional study, with use of spatial analysis and Social Network Analysis (SNA) techniques, conducted in Sobral, a municipality in the state of Ceará. The research population consisted of people under 15 years of age with leprosy (index cases), identified in public health services based on spontaneous demand or by active search in households in areas of hyperendemicity, and also in the screening of leprosy cases in public schools in the municipality and their household contacts (HC) and non-household contacts (NHC). For data collection, in addition to a questionnaire applied to the participants, clinical examination of the skin, skin smear and biopsy of the lesion were performed for positive cases. A rapid test for the detection of specific antibodies against M. leprae was requested for all respondents. Nine new cases of leprosy in children under 15 years of age diagnosed between August 2014 and September 2015 and a total of 151 contacts were studied, of which 36 were HC and 115 NHC. Each index case had 10 to 29 contacts, including HC and NHC. Next, each HC reported having regular contact with six to thirty people and each NHC reported having regular contact with six to 23 people. The contacts named by the HC and NHC formed the indirect contacts (IC) of the index cases and were not interviewed. In the spatial analysis, it was found that the index cases and their non-household contacts were concentrated in poor and hyperendemic areas of the municipality. The spatial analysis also revealed a grouping of subclinical infection in a radius of 102 meters, suggesting that transmission home is not related to proximity to seropositive individuals. At SNA, index cases and their contacts generated a network of 664 people with 1,497 connections between them, including indirect contacts. The index cases and their social contacts constitute nine subnetworks, with people strongly connected to each other and with precarious socioeconomic conditions. Index cases, household and social contacts with reports of leprosy and/or subclinical infection caused by M. leprae, stood out in the social network due to the high values of centrality of degree and intermediation they presented. The study showed that leprosy is present in both household and non-household contacts and that they live in sub- networks with characteristics of a “small world” network, with low socioeconomic status and little education. The investigation of contacts must extend beyond the home, based on the case's social networks.